Left ventricular assist device as a bridge to recovery for patients with advanced heart failure - Jakovljevic,DG; Yacoub,MH; Schueler,S; MacGowan,GA; Velicki,L; Seferovic,PM; Hothi,S; Tzeng,B-H; Brodie,DA; Birks,E; Tan,L-B (Journal of the American College of Cardiology, 2017)
BackgroundLeft ventricular assist devices (LVADs) have been used as an effective therapeutic option in patients with advanced heart failure, either as a bridge to transplantation, as destination therapy, or in some patients, as a bridge to recovery.ObjectivesThis study evaluated whether patients undergoing an LVAD bridge-to-recovery protocol can achieve cardiac and physical functional capacities equivalent to those of healthy controls.MethodsFifty-eight male patients—18 implanted with a continuous-flow LVAD, 16 patients with LVAD explanted (recovered patients), and 24 heart transplant candidates (HTx)—and 97 healthy controls performed a maximal graded cardiopulmonary exercise test with continuous measurements of respiratory gas exchange and noninvasive (rebreathing) hemodynamic data. Cardiac function was represented by peak exercise cardiac power output (mean arterial blood pressure × cardiac output) and functional capacity by peak exercise O2 consumption.ResultsAll patients demonstrated a significant exertional effort as demonstrated with the mean peak exercise respiratory exchange ratio >1.10. Peak exercise cardiac power output was significantly higher in healthy controls and explanted LVAD patients compared with other patients (healthy 5.35 ± 0.95 W; explanted 3.45 ± 0.72 W; LVAD implanted 2.37 ± 0.68 W; and HTx 1.31 ± 0.31 W; p < 0.05), as was peak O2 consumption (healthy 36.4 ± 10.3 ml/kg/min; explanted 29.8 ± 5.9 ml/kg/min; implanted 20.5 ± 4.3 ml/kg/min; and HTx 12.0 ± 2.2 ml/kg/min; p < 0.05). In the LVAD explanted group, 38% of the patients achieved peak cardiac power output and 69% achieved peak O2 consumption within the ranges of healthy controls.ConclusionsThe authors have shown that a substantial number of patients who recovered sufficiently to allow explantation of their LVAD can even achieve cardiac and physical functional capacities nearly equivalent to those of health